A Mild, Thermal Pentafulvene‐to‐Benzene Rearrangement1. Issue 37 (25th July 2013) - Finke, Aaron D.; Haberland, Sophie; Schweizer, W. Bernd; Chen, Peter; Diederich, François
<x xml:space="preserve">Abstract</x> Walk this way: More than 40 years after the discovery that fulvene can thermally rearrange to benzene at high temperatures, it has been found that 6, 6‐dicyanopentafulvenes can rearrange quantitatively to 1, 3‐ and 1, 4‐dicyanobenzenes under mild conditions in polar aprotic solvents. A polar "ring‐walk" mechanism is proposed to explain this unprecedented reactivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>